THE USE OF DIGITAL TECHNOLOGIES IN TEACHING ENGLISH (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This article explores the integration of digital technologies in the process of teaching English as a foreign language. It highlights how modern tools such as interactive applications, online platforms, multimedia content, and virtual learning environments enhance learners’ motivation, engagement, and language acquisition. The study also discusses the advantages and challenges of using digital tools in both traditional and remote classrooms. Special attention is given to how digitalization supports individualized learning and promotes communicative competence among students.